1998
DOI: 10.1126/science.279.5347.49
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Radicals, Nitrogen Radicals, and the Production of O 3 in the Upper Troposphere

Abstract: The concentrations of the hydrogen radicals OH and HO2 in the middle and upper troposphere were measured simultaneously with those of NO, O3, CO, H2O, CH4, non-methane hydrocarbons, and with the ultraviolet and visible radiation field. The data allow a direct examination of the processes that produce O3 in this region of the atmosphere. Comparison of the measured concentrations of OH and HO2 with calculations based on their production from water vapor, ozone, and methane demonstrate that these sources are insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
203
1
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 332 publications
(217 citation statements)
references
References 28 publications
8
203
1
2
Order By: Relevance
“…Studies by Krol et al (6) show a significant global increase in OH, whereas those by Prinn et al (7) show a decline in OH levels after 1988. Recent studies in the upper troposphere also have reported discrepancies between model predictions and measured HO x (where HO X ϵ OH ϩ HO 2 ) concentrations that strongly depend on solar zenith angles (8)(9)(10)(11). These differences between predictions and observation not only highlight the difficulties associated with measuring atmospheric OH concentrations, but also potential variability arising from incomplete accounting of all significant sources and sinks of the OH radical.…”
mentioning
confidence: 93%
“…Studies by Krol et al (6) show a significant global increase in OH, whereas those by Prinn et al (7) show a decline in OH levels after 1988. Recent studies in the upper troposphere also have reported discrepancies between model predictions and measured HO x (where HO X ϵ OH ϩ HO 2 ) concentrations that strongly depend on solar zenith angles (8)(9)(10)(11). These differences between predictions and observation not only highlight the difficulties associated with measuring atmospheric OH concentrations, but also potential variability arising from incomplete accounting of all significant sources and sinks of the OH radical.…”
mentioning
confidence: 93%
“…As a result, measurements of CH 2 O provide a valuable check of photochemical model predictions concerning recent hydrocarbon oxidation [Liu et al, 1992;Lee et al, 1998;Fried et al, 2002Fried et al, , 2003aWert et al, 2003]. In addition, CH 2 O measurements are important to the calculation of accurate OH concentration fields and odd hydrogen (HO x ) budgets [Ayers et al, 1997;Fried et al, 1997a;Wennberg et al, 1998;Jaeglé et al, 2000].…”
Section: Introductionmentioning
confidence: 99%
“…Oxygenated hydrocarbon species have the potential to play an important role in processes of atmospheric ozone formation [Loyd, 1979;Singh et al, 1995;Wennberg et al, 1998]. Unlike most hydrocarbons, many oxygenated species can be photolyzed throughout the troposphere.…”
Section: Introductionmentioning
confidence: 99%